Factors influencing physical activity in individuals with head and neck cancer: a scoping review - Marika Bana; Martina Schmocker; Ramona Engst; Markus Wirz (BMJ Open)
Objectives Higher physical activity (PA) levels are associated with better quality of life in people with head and neck cancer (HNC). Despite this positive association, most individuals with these cancer types have a sedentary or low-activity lifestyle. Limited knowledge exists regarding the factors that influence PA in this group. Therefore, we reviewed and mapped the available literature on factors that may influence PA in people with HNC.Design We conducted a scoping review based on the framework of Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline extension for scoping reviews.Data sources CINHAL, the Cochrane Library, EMBASE, PsycINFO, MEDLINE and Scopus were searched from inception to July 2023.Eligibility criteria We included qualitative and quantitative studies that stated factors such as barriers, facilitators, beliefs, perceptions and views influencing PA in individuals with HNC. Furthermore, views and recommendations of healthcare professionals involved in the care of people affected by HNC and researchers in this domain were eligible for data extraction.Data extraction and synthesis Data were extracted and synthesised by one reviewer according to the predefined items including characteristics, barriers, facilitators, beliefs, perceptions and views of people being affected and views and recommendations of experts. Quantitative data were charted descriptively, and qualitative data were analysed and summarised using a basic content analysis approach.Results Of the 1351 publications, we included 19 in our review. Publications mainly focused on barriers to PA, with some studies reporting facilitators and collecting data on patients’ and healthcare professionals’ views on PA. Most research teams made recommendations for promoting PA in people with HNC.Characteristics associated with activity levels included age, cancer type and stage, morbidity level and attitude towards being active. Prevalent barriers consisted of health-related factors, including fatigue, pain and nutritional issues, alongside personal and environmental impediments such as time constraints, lack of interest or motivation. Facilitating factors for PA included perceived or experienced mental and health-related benefits. Consensus among patients, healthcare professionals and researchers highlighted the necessity for enhanced information and education, emphasising individualised approaches to promote PA throughout the cancer continuum.Conclusions Numerous factors affect PA in individuals with HNC. Future research should concentrate on screening and addressing risk factors for sedentary behaviour and activity barriers and on optimal design and delivery of interventions to incorporate PA promotion into the care pathway.